Organizational culture and change - Phelan, Michael (Henry Stewart Talks, 2009)
What is culture?, Organizational culture versus corporate culture, Integrating within the organization, Disfunctional organizational cultures, Changing organizational culture, Successful change, Kotter and Heskett's model of culture change, Revitalization, Successful leadership